UJI BEBERAPA DOSIS PUPUK ORGANIK CAIR EXTRAK DAUN LAMTORO GUNG DENGAN PEMANGKASAN DAUN PADA PERTUMBUHAN, PRODUKSI JAGUNG HIBRIDA - Makmur Makmur; Muh Rifky Aulia; Arman Arman; Bisri Bisri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2020)
Corn is one of the high economic value food plants which is a good opportunity to be developed. Maize productivity in Indonesia only reaches 4.1 tons / ha at the farm level, the productivity is still low compared to the optimum productivity that can be achieved around 12 tons / ha. The low productivity is due to improper cultivation technology, including the use of chemical fertilizers continuously, therefore we need an effort to use natural fertilizers (organic) and improvement of cultivation technology, one of which is pruning leaves on hybrid corn. This study aims to examine the effect of several doses of liquid organic fertilizer with leaf trimming time, as well as the interaction between the two on hubrida corn. The research was carried out in the Experimental Garden of the Faculty of Agriculture, Unasman, Polewali Mandar District, West Sulawesi Province, from January 2010 to April 2020. The method used was the RAK in factorial form. F1 administration of POC of lamtoro leaf extraction consists of 3 levels, namely: POC of lamtoro leaf extract 100 ml / liter of water, 200 ml / liter of water, and 300 ml / liter of water. Whereas F2 when pruning leaves is: not pruned (control), pruned before the cobs are formed, and trimmed after cobs are formed. The results of this study aimed that the administration of lamtoro leaf extract POC at a dose of 300ml / liter of water had the best effect on plant height variables aged 21 and 42HST, flowering age (days), age of harvest (days), cob length (berkolobat / not kolobot), weight of cob (berkolob / non-berkolobot), and dry weight of 1000 tons / ha conversion items. Furthermore pruning before the formation of the cob gives a good effect on the harvest age variable which is 74 days. While the interaction between the two did not have a real effect on all variables observed.